10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 ...10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 这几提怎么写要过程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 19:16:28
10Y+5=11Y-5+2Y0.4x-1.2_2x=1.2-2.6x2y-5=11-6y2x-1=5x+7...10Y+5=11Y-5+2Y0.4x-1.2_2x=1.2-2.6x2y-5=11-6y
10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 ...10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 这几提怎么写要过程
10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 ...
10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 这几提怎么写要过程
10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 ...10Y+5=11Y-5+2Y 0.4x-1.2_2x=1.2-2.6x 2y-5=11-6y 2x-1=5x+7 这几提怎么写要过程
1:10Y+5=11Y-5+2Y
10Y-11Y-2Y=-5-5
-3Y=-10
Y=0.3
2:0.4X-1.2-2X=1.2-2.6X
0.4X+2.6X-2X=1.2+1.2
X=2.4
3:2Y-5=11-6Y
2Y+6Y=11+5
8Y=16
Y=2
4:2X-1=5X+7
2X-5X=7+1
-3X=8
X=-2(2/3)
1。 10Y+5=9Y-5 10Y-9Y=-10 Y=-10 2。(0.4-2+2.6)X=1.2+1.2 X=2.4 3。 (2+ 6)Y=11+5 Y=2 4。 2x-1=5x+7 (2-5)X=8 X=-8/3
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
(4x-2y-z)-{5x[8y-2y-(x+y)]-x+(3y-10z)]=? kuaihuajian
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
2(x-y)=5y,x-y=-5
x-y / 5y= (y-x)^2 / ( )
例X=1 y=21.X+Y=5 X-Y=15 2.2X+3Y=4 5X+6Y=7 3.X+3Y=5 3X+Y=-1 4.2X+Y=3 3X+5Y=11 5.4X+3Y=6 2X+Y=4 6.X+Y=180 X=3Y-10 7.3X-2Y=3 2X-Y=7 8.5X+3Y=7Y X+Y=45 9.3X+4Y=126X+8Y=24 X:6Y=1:4 10.X+Y=138 X-45=Y+53 11.X+Y=60 14Y=20X 12.2X+3Y=15.5 5X+6Y=35 13.X+Y=170 3
x+y=5① x=3y+2① 9x-5y=1① 3x-2y=11① x-2y=y+1① 2x-y=7② x+3y=8② 6x-7y=2② 2x+3y=16② 2x-3y=10②3x+2y=y+1①2x-3y=10②D
(x+y)/6+(x-y)/10=1,(x+y)/6-(x-y)/10=5
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
x+2y=5x-6y=11
3*X=Y X/2=Y/5+11
{2x+y=74x+5y=11
(x+5y)^+(2x+10y)(3x-y)+(3x-y)^
(x+5y)²-(2x+10y)(3x-y)+(3x-y)²
5x^3y(x-y)^3-10x^4y^3(y-x)^2因式分解
5x^3y(x-y)^3-10x^4y^3(y-x)^2
5X^3Y(X-Y)-10X^4Y^3(Y-X)^2因式分解